Ferroelectric Switching Dynamics of Topological Vortex Domains in a Hexagonal Manganite. (14th March 2013) - Han, Myung‐Geun; Zhu, Yimei; Wu, Lijun; Aoki, Toshihiro; Volkov, Vyacheslav; Wang, Xueyun; Chae, Seung Chul; Oh, Yoon Seok; Cheong, Sang‐Wook
<x xml:space="preserve">Abstract</x> Field‐induced switching of ferroelectric domains with a topological vortex configuration is studied by atomic imaging and electrical biasing in an electron microscope, revealing the role of topological defects on the topologically‐guided change of domain‐wall pairs in a hexagonal manganite. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>